Characteristics of Pregnant Women with Oligohydramnions Treated with Amnioinfusion at d DR. M. Djamil Padang - Rahman, Andio; Yusrawati (Fakultas Kedokteran Universitas Andalas, 2023)
Introduction : Oligohydramnios is a condition of reduced amniotic fluid. This is often detected accidentally during ultrasonography examination so that there is often a delay in diagnosis. Amnioinfusion is one of the therapies given to pregnant women with oligohydramnios Aim: This study aims to determine the characteristics of pregnant women with oligohydramnios who are treated with amnioinfusion Method: This was a descriptive study using medical record data of inpatients at the Fetomaternal Polyclinic, Dr. M. Djamil Hospital Padang from March 2022 to March 2023. The inclusion criteria were pregnant women diagnosed with oligohydramnios and the exclusion criteria were multiple pregnancies. Sampling was done by total sampling. Result: There were 12 pregnant womens who met the inclusion and exclusion criteria. Most of the subject aged 20-35 years (91.7%), high school graduates (58.3%), and multiparous (66.7%). There are as many as 50% of fetuses with congenital abnormalities. Most of the oligohydramnios were diagnosed in the third trimester (83.3%). Pregnant women with oligohydramnios have a relatively high proportion of preterm births (41.7%). Most of the subject still have good fetal outcome (alive) (66.7%). Conclusion: Pregnant women with oligohydramnios had age, education and parity who were not at high risk but more often had fetuses with congenital abnormalities and premature births. Amnioinfusion reduces fetal mortality